Strategi Pendidikan Life Skill Di Pondok Pesantren Dalam Meningkatkan Kemandirian Santri - Muttaqin, M Nur Shidiq; Malik, Fatkhulloh Abdul; Fikri, Akhmad Kanzul (JoEMS (Journal of Education and Management Studies), 2022)
The Islamic boarding school which is so loved by the community is traditionalist, namely to explore the Islamic religious sciences as a way of life by emphasizing the importance of morals and ethics in society, even for the qualified life skills for students. This absolutely must be developed by a boarding school so that its existence remains strong and not eroded by an era that is oriented towards productive things. The main questions in this study are (1) How is the concept of life skills education at the level of experts? (2) How are the life skills education efforts at the pesantren to increase the independence of the Al Hikmah Bahrul Ulum Islamic boarding school students? (3) What are the factors that support and hinder efforts to educate life skills at the pesantren in increasing the independence of the students of the Al Hikmah BahrulUlum Islamic boarding school? Researchers used qualitative research methods using interview methods, observation and documentation at the alhikmah Islamic boarding school. The research results were (1) The concept of life skills education according to Anwar. The concept of life skills is the skill or ability to adapt and behave positively, which allows a person to be able to face various demands and challenges in his daily life effectively. (2) Efforts to increase the independence of the boarding school santri al-Hikmah through life skills; with the existence of regulations - wardrobe, individual activities such as washing clothes by yourself, managing your own finances, cleaning your own bedroom and cooking by yourself too. Meanwhile, (3) factors that support the success of life skills; The students' interest in the education provided, the availability of adequate facilities, the support of the government and the community around the boarding school, supported by good capital. Factors inhibiting the success of life skills; shortage of skilled teaching staff, lack of capital, unclear regulations and lack of discipline, the laziness of the students and the lack of interest among the students.